Nature and community: Toward a Marcusean-informed environmentalism. - Chisholm, Mariellen. (University of Ottawa (Canada), 1993)
Concern for the environment is a theme which has gained much currency in popular and academic discourse. The normative assumptions, however, which underlie the field of environmental politics, are far from univocal. The exclusion of normative considerations from much environmental literature and many environmental projects, therefore, is an indication of our general failure to see environmental issues as ethical issues demanding resolution. This study aims at examining how the critical theory of Herbert Marcuse contributes to an ecological perspective that does treat the natural environment as a domain of ethical inquiry. Drawing from the Romantic tradition, Marcuse treats nature as sensuousness and spirituality with immanent value. His theory of nature is concerned with the reconciliation of human subjectivity as rational, moral will with external nature. What emerges is an ethics of aesthetic community in which nature is more than an object of contemplation, but the purveyor of immanent value, the grounds for ethical, creative and "playful" activity. This notion of aesthetic community does not emerge without its own internal tension and ambiguity which, we argue in this work, remain unresolved as a synthesis of subjective aesthetic judgment and collective reason. In spite of the tension, we conclude that the Marcusean spiritual sensitivity and rational interest could more fruitfully serve as a more solid foundation for contemporary environmentalism and ecological theory.
Keywords: Philosophy.